2022
DOI: 10.1007/s11881-022-00274-0
|View full text |Cite
|
Sign up to set email alerts
|

Perceived negative consequences of dyslexia: the influence of person and environmental factors

Abstract: Perceived negative consequences of dyslexia entail the degree to which an individual perceives negative outcomes, such as low academic achievement or feelings of anxiety and depression, and attributes these experiences to the disorder. In the current study, we examined how perceived consequences of dyslexia are influenced by person and environmental factors. Perceived consequences were evaluated for the academic domain and the domain of mental health (depression, anxiety). Participants were 123 Dutch students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
(111 reference statements)
1
4
0
Order By: Relevance
“…In addition to resilience, both avoidance-oriented and emotion-oriented coping were associated with poorer mental health, and in particular, groups with MD reported higher levels of these less functional coping styles. The hierarchical regression analyses indicated that emotion-oriented coping significantly contributed to adult-age mental well-being, which confirms the results of previous studies (Alexander-Passe, 2006 ; Bazen et al, 2023 ; Carroll & Iles, 2006 ). It is plausible that individuals experiencing more mental problems are also prone to react emotionally—that is, emotion-oriented coping could be an indicator of their mental stress.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In addition to resilience, both avoidance-oriented and emotion-oriented coping were associated with poorer mental health, and in particular, groups with MD reported higher levels of these less functional coping styles. The hierarchical regression analyses indicated that emotion-oriented coping significantly contributed to adult-age mental well-being, which confirms the results of previous studies (Alexander-Passe, 2006 ; Bazen et al, 2023 ; Carroll & Iles, 2006 ). It is plausible that individuals experiencing more mental problems are also prone to react emotionally—that is, emotion-oriented coping could be an indicator of their mental stress.…”
Section: Discussionsupporting
confidence: 89%
“…A clearer understanding of the variations in mental health outcomes requires research on psychological processes, experiences, and the meanings attached by an individual to the difficulty; longitudinal data and qualitative or mixed-method approaches would possibly provide more profound comprehension than data based on questionnaires. A broader perspective, including diverse comorbidities and environmental aspects in addition to personal and socio-emotional factors, is needed as well (e.g., Bazen et al, 2023 ). The present findings underscore the need to prevent adult-age mental health problems, especially among people with childhood MD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has indicated that poor readers at university perceived that their literacy difficulties would have negative academic and mental health (incl. anxiety) consequences, which was not fully accounted for by their literacy difficulties when measured objectively (Bazen et al, 2022 ). As such, it appears that there is a discrepancy between the perceived and actual impact of reading difficulties amongst poor readers.…”
Section: Discussionmentioning
confidence: 99%
“…With more demanding postsecondary coursework and expectations, it is not surprising that in comparison to their non‐dyslexic peers, AWD experience higher levels of academic anxiety (Abbott‐Jones, 2022; Bazen et al, 2023; Lithari, 2018), lower frustration tolerance (Potard et al, 2022), low academic self‐efficacy (Brunswick & Bargary, 2022; Stagg et al, 2018), internalizing problems such as low self‐esteem, depression and somatic discomfort (Bazen et al, 2023; Ghisi et al, 2016), exhaustion (Gant & Hewson, 2022), lower life satisfaction (Kalka & Lockiewicz, 2018), and perfectionism and self‐stigma (Stoeber & Rountree, 2021). Abbott‐Jones (2022) suggests that for students to navigate the trials of college successfully, cognitive and emotional coping skills are essential.…”
Section: Literature Reviewmentioning
confidence: 99%